Erratum (Journal of Comments and Replications in Economics (JCRE), 2024)
In a recent publication of this journal, Joan Barceló published a reply (JCRE, Vol.3, 2024-7) challenging the results of a replication study by Edmund Malesky and Trung-Anh Nguyen (JCRE, Vol.3, 2024-5). At issue is whether US bombing in Vietnam caused greater civic engagement among those Vietnamese who personally experienced bombing. Barceló (2021, 2023) claims that it did. Malesky and Nguyen (MN) argue that a combination of errors invalidates his conclusion. Barceló's reply in the JCRE pushes back against MN's arguments. Interested readers wanting to know more details may want to read the articles by Barceló and MN in this journal. It is not the purpose of JCRE to adjudicate differences between researchers. Our goal is merely to provide a platform for researchers to confirm or disconfirm published research. As a result, the practice of JCRE is to publish a replication and allow the original author the opportunity to reply. And then that is it. We do not publish replies to replies and subsequent responses. However, JCRE has become aware that a claim made in Barceló's reply rests on two coding mistakes. When those coding mistakes are corrected, this claim is no longer supported. We underscore that these mistakes do not undermine all of Barceló's claims. The remainder of this erratum explains the coding mistakes and how they impact the debate.
https://doi.org/10.15456/j1.2024314.0652207104
Keywords: 330